A framework for understanding semi‐permeable barrier effects on migratory ungulates. Issue 1 (5th December 2012) - Sawyer, Hall; Kauffman, Matthew J.; Middleton, Arthur D.; Morrison, Thomas A.; Nielson, Ryan M.; Wyckoff, Teal B.; Pettorelli, Nathalie
Summary Impermeable barriers to migration can greatly constrain the set of possible routes and ranges used by migrating animals. For ungulates, however, many forms of development are semi‐permeable, and making informed management decisions about their potential impacts to the persistence of migration routes is difficult because our knowledge of how semi‐permeable barriers affect migratory behaviour and function is limited. Here, we propose a general framework to advance the understanding of barrier effects on ungulate migration by emphasizing the need to (i) quantify potential barriers in terms that allow behavioural thresholds to be considered, (ii) identify and measure behavioural responses to semi‐permeable barriers and (iii) consider the functional attributes of the migratory landscape (e.g. stopovers) and how the benefits of migration might be reduced by behavioural changes. We used global position system (GPS) data collected from two subpopulations of mule deer Odocoileus hemionus to evaluate how different levels of gas development influenced migratory behaviour, including movement rates and stopover use at the individual level, and intensity of use and width of migration route at the population level. We then characterized the functional landscape of migration routes as either stopover habitat or movement corridors and examined how the observed behavioural changes affected the functionality of the migration route in terms of stopover use. We found migratory behaviour to vary with development intensity. Our results suggest that mule deer can migrate through moderate levels of development without any noticeable effects on migratory behaviour. However, in areas with more intensive development, animals often detoured from established routes, increased their rate of movement and reduced stopover use, while the overall use and width of migration routes decreased. Synthesis and applications. In contrast to impermeable barriers that impede animal movement, semi‐permeable barriers allow animals to maintain connectivity between their seasonal ranges. Our results identify the mechanisms (e.g. detouring, increased movement rates, reduced stopover use) by which semi‐permeable barriers affect the functionality of ungulate migration routes and emphasize that the management of semi‐permeable barriers may play a key role in the conservation of migratory ungulate populations.